Getting secondary school students engaged in reading activities: adoption of anecdotes to elevate their reading skills - Haris Hamdani (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2022)
The present study aims to examine the effect of adopting anecdotes on senior high school students’ reading skill. Nested in mix-research methods, data were garnered through test and interview. The data obtained from the test were analyzed statistically. The study findings reveal that the average score for the application of anecdote was 7.3 which belonged to category “sufficient”. Meanwhile, the average score of students’ reading skills is 6.8. It was classified into the category “sufficient” Pearson's Product Moment Correlation formula yielded 0.42 for the calculation of the correlation between the X and Y variables. The variable X was the adoption of anecdotes, and the variable Y was students’ reading skills. The statistical calculation demonstrates that the product moment correlation score of 0.42 can be interpreted as “moderate correlation”. It indicates that there was significant effect of using anecdotes on the senior high school students’ reading skills. This study concludes with empirical evidence on how EFL senior high school teachers adopt anecdotes for their reading classrooms.